AN ANALYSIS OF TEACHERS' STRATEGY IN TEACHING READING COMPREHENSION - Anisa Ardianti; Monalisa; Amalia, Shynta (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
This research aimed to determine the strategies used by English teachers in teaching reading comprehension and how they apply these strategies. This research was designed as descriptive qualitative research. The research was conducted at SMAN 02 Muaro Jambi. The participants of this research were three English teachers who taught in the tenth (X) MIPA grade of the school. Due to the COVID-19 pandemic so, each English teachers had two meetings observed by the researcher. The research instrument is an observation and interview. The instrument used is to find out the strategies used and how the English teachers applies the strategies in teaching reading comprehension. The results of the data were analyzed by; checklist observations and field notes. The results showed that the teacher used several strategies in teaching reading comprehension. The strategies are Translation strategy, Scaffolding strategy, and Question and Answer Relationship Strategy. Encourage the use of dictionaries, rereading to assess comprehension, understanding in certain tasks, and asking questions for specific information strategies applied in implementing reading comprehension in the school. This is evidenced by the motivation of students, students’ attention, and the ease of teachers in teaching and learning process